Effects of gut microbiota on prostatic cancer: a two-sample Mendelian randomization study - Xie, Qingpeng; Hu, Bin (Frontiers in Microbiology, 2023)
Aim: Recent observational and small sample case-control studies have showed a relationship between gut microbiota composition and prostatic cancer (PCa).Nevertheless, the causal association between gut microbiota and PCa is still unclear.Herein, we used the Mendelian randomization (MR) method to explore the potential causal relationship between gut microbiota and PCa.In this two-sample MR study, data were extracted from the summary statistics of gut microbiota from the largest available genome-wide association study (GWAS) meta-analysis conducted by the MiBioGen consortium (n=14306) and Dutch Microbiome Project (DMP) (n=8208). Summary statistics of PCa were obtained from the FinnGen consortium release data (n=95213). Inverse variance weighted (IVW), MR-Egger, strength test (F), and MR-PRESSO were used to examine the potential causal association between gut microbiota and PCa. Cochran's Q statistics were used to quantify the heterogeneity of instrumental variables.Results: IVW estimates suggested that the relative abundance of Akkermansia muciniphila (OR=0.7926, 95%CI: 0.6655-0.9440) and Bacteroides salyersiae (OR=0.9023, 95%CI: 0.8262-0.9853) were negatively associated with the odds of PCa, while that of Eubacterium biforme (OR=1.1629, 95%CI: 1.0110-1.3376) was positively associated with the odds of PCa. Also, we explored these relationships among patients without other cancers, and similarly found that the relative abundance of Akkermansia muciniphila, Bacteroides salyersiae, and Eubacterium biforme were linked to PCa (all P<0.05).Effects of gut microbiota on PCa 3 Conclusions: Gut microbiota potentially influenced the occurrence of PCa. Our findings may provide some new ideas for researching the methods of PCa prevention.In addition, further studies are needed to explore the causal association and specific underlying mechanisms between gut microbiota and PCa.